Improving Cadet Discipline And Character Through Time Management At The Official School Of The Transportation Human Resources Development Agency - Muhammad Caesar Akbar; Grecia Enzelica (Yayasan Multidimensi Kreatif, 2024)
Education in institutions such as the Transportation Human Resources Development Agency (BPSDMP) has a crucial role in forming the character and discipline of cadets. One effective approach in achieving this goal is through implementing good time management. Time management not only helps cadets in completing tasks efficiently, but also contributes to the formation of self-discipline and strong character. This study uses a qualitative descriptive method to explore the implementation of time management in BPSDMP and its impact on cadet discipline and character. Data was obtained through observation, interviews and collecting information from various sources. The research results show that effective time management allows cadets to organize their daily activities well, follow a strict schedule, and meet deadlines consistently. The application of time management at BPSDMP also has an impact on developing the character of cadets. They are taught to be responsible, work hard, and not give up easily in facing challenges. Cadet achievements in various fields such as academics and sports are clear evidence of the effectiveness of time management in forming strong character and high discipline. Case studies of several cadets who achieved achievements confirmed that the time management implemented at BPSDMP was successful in forming cadets who were disciplined and had strong character. Cadets are trained to value time, set goals, and work hard to achieve them. Their success does not only reflect academic or sporting achievements, but also the formation of character that is ready to face various challenges in the future. Implementing good time management at BPSDMP is a strategic step in forming cadet discipline and character. With high discipline and strong character, the cadets are expected to become future leaders with integrity and able to face various challenges in the world of work and everyday life.